2009
DOI: 10.2147/opth.s4684
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of cystoid macular edema with the new-generation NSAID nepafenac 0.1%

Abstract: Purpose:To describe the use of nepafenac 0.1% for cystoid macular edema (CME).Methods:This was a multicenter retrospective review of 22 CME cases (20 patients) treated with nepafenac 0.1% (six with concomitant prednisolone acetate 1%) from December 2005 to April 2008: three acute pseudophakic CME cases, 13 chronic/recalcitrant pseudophakic CME cases, and six cases of uveitic CME. Pre- and post-treatment retinal thickness and visual acuity were reported.Results:Following treatment for six weeks to six months, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 25 publications
1
46
0
1
Order By: Relevance
“…Optical coherence tomography has also been used to diagnose, assess, and monitor the therapeutic response in uveitic macular edema [48,51,[69][70][71][72][73][74][75][76][77][78][79][80][81][82][83][84][85]. In a recent study, Sugar et al [86] tried to identify a clinically meaningful threshold for change in uveitic macular edema evaluated by OCT. A 20 % change in retinal thickness in patients with uveitic macular edema was found to be optimal for clinically important changes in visual acuity.…”
Section: Use Of Optical Coherence Tomography Technology In Uveitis Prmentioning
confidence: 99%
“…Optical coherence tomography has also been used to diagnose, assess, and monitor the therapeutic response in uveitic macular edema [48,51,[69][70][71][72][73][74][75][76][77][78][79][80][81][82][83][84][85]. In a recent study, Sugar et al [86] tried to identify a clinically meaningful threshold for change in uveitic macular edema evaluated by OCT. A 20 % change in retinal thickness in patients with uveitic macular edema was found to be optimal for clinically important changes in visual acuity.…”
Section: Use Of Optical Coherence Tomography Technology In Uveitis Prmentioning
confidence: 99%
“…Nepafenac has been reported to be effective against macular edema of various etiologies, including acute and chronic pseudophakic CME, uveitic CME, diabetic macular edema and postoperative CME. 4,[7][8][9] Our case demonstrated that topical nepafenac is effective in the treatment of CME secondary to radiation therapy. Following treatment, there was rapid and complete resolution of macular edema and improvement in vision.…”
Section: Discussionmentioning
confidence: 65%
“…Several studies have previously reported the beneficial effects of nepafenac in treating CME. 3,4 We hereby report the use of topical nepafenac in a patient with CME secondary to radiation therapy for choroidal metastasis. Treatment resulted in prompt reduction in CME with visual improvement.…”
Section: Introductionmentioning
confidence: 99%
“…We used low-molecular-weight-heparin (enoxaparin) in the treatment of this patient, according to the ophtalmologist's suggestions. Also, a topical non-steroidal anti-inflammatory agent (nepafenac 0.1%) was administered, to reduce macular edema until the venous occlusion resolved (6). The patient's macular edema was minimally cystoid so no other treatments were considered.…”
Section: Discussionmentioning
confidence: 99%